ANALISIS FAKTOR FUNDAMENTAL PADA HARGA SAHAM (Studi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi) - Puja Aunun Fauziah; Hadi Ismanto (Jurnal Dinamika Ekonomi & Bisnis, 2018)
This study analyzes the influence of the company's fundamental factors including asset structure, total asset turnover, dividend policy, and earnings per share on the stock prices of manufacturing companies. The research sample of 32 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2012-2015 using purposive sampling technique. Panel data were analyzed using Eviews 9 with Chow-test to obtain good regression results. The results showed that a combination of fundamental factors influenced fluctuations in stock prices. Although partially, asset structure and total asset turnover are not significant to stock prices, a positive correlation is shown by dividend and earnings per share policies on changes in stock prices.